A novel porous Fe3O4/Titanosilicate/g-C3N4 ternary nanocomposites: Synthesis, characterization and their enhanced photocatalytic activity on Rhodamine B degradation under sunlight irradiation. (April 2020) - Adepu, Ajay Kumar; Siliveri, Suresh; Chirra, Suman; Goskula, Srinath; Gujjula, Sripal Reddy; Anumula, Rajini; Narayanan, Venkatathri
Abstract: A magnetically separable Fe3 O4 /porous Titanosilicate/g-C3 N4 hybrid nanocomposite (FTSCN) has been synthesized by a facile in-situ method. The synthesized nanocomposites are characterized by PXRD, FE-SEM, TEM, BET-Surface area, FT-IR, UV–vis., photoluminescence, magnetic susceptibility and photocatalytic activity. XRD, FE-SEM, TEM, FT-IR, results of FTSCN show that the formation of finely distributed Fe3 O4 nanoparticles in the titanosilicate matrix and g-C3 N4 . BET-surface area shows that the enhancement of surface area on heterojunction. The bandwidth is calculated from diffuse reflectance ultraviolet-visible spectroscopy. The enhancement of electron-hole pair formation is observed fluorescence spectroscopy. The magnetic behaviour is also observed by magnetic susceptibility test of the nanocomposite. FTSCN nanocomposite exhibit improved photodegradation of Rhodamine B sunlight light irradiation. The ideal photocatalytic activity of FTSCN3.5 in presence of sunlight is nearly 4 to 5-fold greater than pure Fe3 O4 (FO), pure titanosilicate (TS) and g-C3 N4 respectively. We confirmed that the prepared FTSCN3.5 hybrid photocatalyst is very stable even after five consecutive trial runs are observed by XRD spectral data. The enhanced photocatalytic behaviour of the FTSCN3.5 hybrid nanocomposite in the presence of sunlight is because of the synergistic effect of the Fe3 O4, pure titanosilicate and g-C3 N4 . A plausible, structure of heterojunction, physical and chemical catalytic mechanisms are also proposed.